620 Tumor cell-intrinsic STING pathway is activated in the presence of cues from immune cells and contributes to the anti-tumor activity of tumor cell-targeted STING agonist antibody-drug conjugates. (9th November 2020) - Cetinbas, Naniye Malli; Monnell, Travis; Lee, Winnie; Catcott, Kalli; Chin, Chen-Ni; Shaw, Pamela; Slocum, Kelly; Qin, LiuLiang; Avocetien, Kenneth; Bentley, Keith; Clardy, Susan; Jones, Brian; et al.
Abstract : Background: STING pathway agonism has emerged as a potential therapeutic mechanism to stimulate an innate anti-tumor immune response. While in principle systemic administration of a STING agonist would have many therapeutic benefits, including the delivery of STING to all tumor lesions, such an approach may be limited by toxicity. Antibody-drug conjugates (ADCs) constitute a proven therapeutic modality that is ideally suited to allow systemic administration while stimulating the innate immunity in a targeted manner. We have previously demonstrated that targeted delivery of a STING agonist with an ADC induces robust anti-tumor immune responses. Methods: Herein we investigated the mechanism of action of tumor cell-targeted STING agonist ADCs. We evaluated STING pathway activation and anti-tumor activity elicited by ADCs harboring either wild type (wt) or mutant Fc deficient in Fcγ receptor (FcγR) binding in wt or STING knockout (ko) cancer cell mono-cultures, immune cell co-cultures, and in in vivo tumor models. Results: Consistent with previous reports, the majority of cancer cell lines tested failed to induce STING pathway following STING agonist payload treatment in mono-cultures. In cancer cell:THP1 monocytic cell co-cultures, tumor-targeted STING agonist ADCs with wt Fc exhibited robust STING activation, whereas Fc-mutant ADCs or non-targeted control ADCs had minimal activity. Similar results were obtained when THP1 cells were treated in plates coated with target antigen without cancer cells, demonstrating STING activation in THP1 cells following FcγR-mediated uptake of antigen-bound ADCs. Tumor-targeted Fc-wt ADCs led to marked induction of STING pathway and cancer cell-killing in cancer cell:PBMC or primary monocyte co-cultures, and complete tumor regressions in in vivo tumors. Surprisingly, while at reduced levels relative to the Fc-wt ADCs, Fc-mutant ADCs exhibited significant activity in these in vitro and in vivo models, suggesting that tumor cell-intrinsic STING pathway may be activated in the presence of cues from immune cells. Consistently, STING agonist payload treatment in the presence of conditioned media from PBMC and primary monocyte but not from THP1 cultures, led to STING activation in cancer cell mono-cultures. Moreover, Fc-mutant ADCs had diminished activity in STING ko cancer cell:PBMC or primary monocyte co-cultures, demonstrating the contribution of tumor cell-intrinsic STING activation to the anti-tumor activity elicited by tumor cell-targeted STING agonist ADCs. Conclusions: In conclusion, we demonstrated that tumor cell-targeted STING agonist ADCs induce robust anti-tumor activity through mechanisms involving both FcγR and tumor antigen-mediated ADC internalization and subsequent induction of STING pathway in immune cells and tumor cells.